Software Engineering and Formal Methods : SEFM 2014 Collocated Workshops: HOFM, SAFOME, OpenCert, MoKMaSD, WS-FMDS, Grenoble, France, September 1-2, 2014, Revised Selected Papers - Canal, Carlos; Idani, Akram; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes revised selected papers from the workshops collocated with the SEFM 2014 conference on Software Engineering and Formal Methods, held in Grenoble, France, in September 2014. The 26 papers included in this volume were carefully reviewed and selected from 49 submissions. They are from the following workshops: the 1st Workshop on Human-Oriented Formal Methods - From Readability to Automation, HOFM 2014, the 3rd International Symposium on Modelling and Knowledge Management Applications - Systems and Domains, MoKMaSD 2014, the 8th International Workshop on Foundations and Techniques for Open Source Software Certification, Open Cert 2014, the 1st Workshop on Safety and Formal Methods, SaFoMe 2014 and the 4th Workshop on Formal Methods in the Development of Software, WS-FMDS 2014.
HOFM 2014 -- A Usability Evaluation of Interactive Theorem Provers Using Focus Groups -- An Approach for Creating Domain Specific Visualisations of CSP Models -- Using Z in the Development and Maintenance of Computational Models of Real-World Systems -- When a Formal Model Rhymes with a Graphical Notation -- SaFoMe 2014 -- On a Process Algebraic Representation of Sequence Diagrams -- Modelling and Verification of Survivability Requirements for Critical Systems -- Model-Based Verification of Safety Contracts -- A Testing-Based Approach to Ensure the Safety of Shared Resource Concurrent Systems -- A Contracts-Based Framework for Systems Modeling and Embedded Diagnostics -- OpenCert 2014 -- Modelling and Verifying Smell-Free Architectures with the ARCHERY Language -- OntoLiFLOSS: Ontology for Learning Processes in FLOSS Communities -- Process Mining Event Logs from FLOSS Data: State of the Art and Perspectives -- MoKMaSD 2014 -- A Latent Representation Model for Sentiment Analysis in Heterogeneous Social Networks -- Use of Mobile Phone Data to Estimate Visitors Mobility Flows -- An Abstract State Machine (ASM) Representation of Learning Process in FLOSS Communities -- A Mathematical Model for Assessing KRAS Mutation Effect on Monoclonal Antibody Treatment of Colorectal Cancer -- Sea-Scale Agent-Based Simulator of Solea solea in the Adriatic Sea -- Research Challenges in Modelling Ecosystems -- Retrieving Points of Interest from Human Systematic Movements -- WS-FMDS 2014 -- Path-Sensitive Race Detection with Partial Order Reduced Symbolic Execution -- Phase-Type Approximations for Non-Markovian Systems: A Case Study -- Quantitative Anonymity Evaluation of Voting Protocols -- Scalable Verification of Markov Decision Processes -- Towards Synthesis of Attack Trees for Supporting Computer-Aided Risk Analysis -- On Generation of Context-Abstract Plans -- A Coloured Petri Net Approach to Model and Analyse Stateful Workflows Based on WS-BPEL and WSRF.
Keywords: Logic design; Software engineering; Computer science; Logics and Meanings of Programs; Software Engineering; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages